Electron density functions for simple molecules - Pearson, Ralph G. (1980)
Trial electron density functions have some conceptual and computational advantages over wave functions. The properties of some simple density functions for H(+)(2) and H(2) are examined. It appears that for a diatomic molecule a good density function would be given by ρ = N(A(2) + B(2)), in which A and B are short sums of s, p, d, etc. orbitals centered on each nucleus. Some examples are also given for electron densities that are appropriate for excited states.